Drug Release Properties of a Series of Adenine‐Based Metal–Organic Frameworks. Issue 47 (25th September 2015) - Oh, Hyojae; Li, Tao; An, Jihyun
Abstract: The drug uptake and release properties of a series of biomolecule‐based metal–organic frameworks (bMOF‐1, bMOF‐4, bMOF‐100, and bMOF‐102) have been studied. The bMOFs were loaded with the small molecule etilefrine hydrochloride and release profiles were collected in both Nanopure water and simulated body fluid (SBF). Each bMOF exhibited an initial burst of drug release at the initial stages of the experiment followed by a gradual release of the remaining drug molecules over time. bMOF‐1 released 50 % of the drug after 15 days and complete release at 80 days in SBF. bMOF‐4 released 50 % of the drug within two days and complete release at 49 days in SBF. bMOF‐100 and bMOF‐102 released 50 % of the drug after 4 h and complete release at 69 and 54 days in SBF, respectively. Abstract : Steady release : The drug uptake and release properties of a series of biomolecule‐based metal–organic frameworks (bMOF‐1, bMOF‐4, bMOF‐100, and bMOF‐102) have been studied (see figure). The bMOFs were loaded with the small molecule etilefrine hydrochloride and release profiles were collected in both Nanopure water and simulated body fluid (SBF).